Modeling the impact of small plasma proteins on stabilization and destabilization of blood - Rahmat Darani Guotama (2010)
There are many publications that report the presence of small polymer can affect the red blood cell aggregation induced by larger polymer. However the studies with the goal to find the mechanism or mechanisms on how small polymer can affect the red blood cell aggregation are still lacking. This paper has modeled the effect of small polymer in the binary solutions containing the variation of DEX 70 and PEG 35 as the large polymers, DEX 10, DEX 20, PEG 3.4, PEG 7.5 and PEG 10 as a small polymer. The model developed in this paper is based on the previously developed depletion-mediated model. The calculated result shows qualitative and quantitative agreement with the available experimental data. This model will help the understanding on how small polymer affects cell-cell aggregation.